Asset-Based Community Development for Employee Performance Enhancement by Leveraging Personality and Job Satisfaction - Purba, Bernanda; Nizamuddin, Nizamuddin (PT Agung Media Publisher, 2025)
This study examines the impact of personality and job satisfaction on employee performance at the Directorate of Commercial Order, Ministry of Trade of the Republic of Indonesia. The research employs a quantitative approach using Structural Equation Modeling (SEM) with AMOS software for data analysis. A total of 141 employees were surveyed using a census sampling method. The results reveal that personality has a significant positive effect on employee performance, indicating that traits such as conscientiousness and emotional stability enhance work outcomes. Similarly, job satisfaction significantly influences performance, emphasizing the importance of workplace conditions, compensation, and career development in boosting employee productivity. Furthermore, job satisfaction partially mediates the relationship between personality and performance, demonstrating that satisfied employees are more likely to translate their personality traits into high performance. The findings align with the Asset-Based Community Development (ABCD) approach, which suggests that organizations should focus on optimizing employees' intrinsic strengths rather than merely addressing weaknesses. By fostering a work environment that enhances job satisfaction, organizations can maximize employee contributions and overall performance. Despite its contributions, this study has limitations, including the scope of variables and the sample size confined to one directorate. Future research should explore additional factors such as leadership style, organizational culture, and work-life balance. Expanding the sample to include different institutions and industries could improve generalizability. Moreover, longitudinal studies are recommended to assess long-term behavioral patterns. This study provides valuable insights for policymakers and organizational leaders in enhancing employee performance through personality development and job satisfaction strategies.